Fiscal Sustainability and its Impact on Financial Stability in Lithuania and other New Member States of the European Union - Keliuotytė-Staniulėnienė, Greta (Ekonomika, 2015)
Financial stability is related to both the real economic sector and public finance stability, and this cohesion is complex, ambiguous, especially complicated, includes many factors acting in different directions. Fiscal sustainability is one of the most significant factors of financial stability, and recently its significance has unfolded in the context of increasing fiscal imbalances and the government debt crisis. The growing interdependence between the public and the financial sectors leads to strengthening the two-direction connection between fiscal sustainability and financial stability. This article analyses one direction of this connection, i. e. implications of fiscal sustainability for financial stability. The complex research presented in this article involves the analysis of scientific literature, of statistical data, multi-criteria evaluation, the interstate comparative analysis, and panel estimation. The results of the research show that some fiscal variables may have a role to play in explaining changes of the financial stability index.